2023
DOI: 10.3390/nu15234885
|View full text |Cite
|
Sign up to set email alerts
|

Hydration for Adult Patients with Nephrolithiasis: Specificities and Current Recommendations

Marie Courbebaisse,
Simon Travers,
Elise Bouderlique
et al.

Abstract: Nephrolithiasis affects around 10% of the population and is frequently associated with impaired dietary factors. The first one is insufficient fluid intake inducing reduced urine volume, urine supersaturation, and subsequently urinary lithiasis. Kidneys regulate 24 h urine volume, which, under physiological conditions, approximately reflects daily fluid intake. The aim of this study is to synthesize and highlight the role of hydration in the treatment of nephrolithiasis. Increasing fluid intake has a preventiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 105 publications
0
1
0
Order By: Relevance
“…Many studies have shown that low urine volume is a risk factor for kidney stones, and adequate intake of drinking water can prevent kidney stone formation. A large amount of water intake can dilute the concentration of urine, prevent the formation of crystals of uric acid, oxalate, and other chemical components in urine, and promote their excretion ( 41 - 44 ). However, unexpectedly, the MR analysis in our study did not show a significant association between water intake and kidney or ureteral stones, although water intake was found to reduce the risk of bladder and other lower urinary tract stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that low urine volume is a risk factor for kidney stones, and adequate intake of drinking water can prevent kidney stone formation. A large amount of water intake can dilute the concentration of urine, prevent the formation of crystals of uric acid, oxalate, and other chemical components in urine, and promote their excretion ( 41 - 44 ). However, unexpectedly, the MR analysis in our study did not show a significant association between water intake and kidney or ureteral stones, although water intake was found to reduce the risk of bladder and other lower urinary tract stone formation.…”
Section: Discussionmentioning
confidence: 99%